2019
DOI: 10.1021/acs.energyfuels.8b03468
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Effect of Fuel Deoxygenation and Polar Species Removal on Jet Fuel Surface Deposition

Abstract: The effect of near-complete deoxygenation and polar species removal on deposition 3 propensity of a Jet A-1 fuel type, with marginal thermal oxidative stability was studied 4 in a laboratory scale approach. The fuel deoxygenation was carried out via nitrogen 5 purging and two types of bespoke zeolites were used separately in a packed bed reactor 6 for partial polar separation. The treated fuel samples were assessed individually for 7 deposition propensity, using "High Reynolds Thermal Stability(HiReTS)" test d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…. 11 Our quantum chemistry calculations suggested that the probability of this class of reaction, during the autoxidation, is higher than that of the thermal decomposition reaction. The self-reaction of hydro- peroxides is also suggested by Bateman et al 12 for the liquid phase autoxidation of hydrocarbons.…”
Section: ■ Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…. 11 Our quantum chemistry calculations suggested that the probability of this class of reaction, during the autoxidation, is higher than that of the thermal decomposition reaction. The self-reaction of hydro- peroxides is also suggested by Bateman et al 12 for the liquid phase autoxidation of hydrocarbons.…”
Section: ■ Introductionmentioning
confidence: 83%
“…It is interesting to note that the maximum uptake of the oxygenated species was approximately the same as in the case of the adsorption in the packed bed of zeolite, as shown in our previous work. 11 However, the rate of adsorption of this class of species was slower in the combined packed bed.…”
Section: Table 2 Test Conditions In Hiretsmentioning
confidence: 99%
See 2 more Smart Citations
“…In advanced aircraft, the aviation fuel is not only used as a power source but also as a primary coolant in the onboard thermal management system to remove excessive heat load. During the heat exchange process, the temperature of the jet fuel increases and when it reaches about 150 °C, the hydrocarbons in the fuel will begin to react with dissolved oxygen to produce thermal oxidation deposition. , This will cause severe problems to the aeroengine, for example, it will block the tubes, nozzles, and valves, affect the heat exchange system, and may eventually even cause flight accident. …”
Section: Introductionmentioning
confidence: 99%